IMPLEMENTASI BUDAYA SEKOLAH DALAM MEMBANGUN KARAKTER RELIGIUS PESERTA DIDIK DI SMAN I SEUNAGAN NAGAN RAYA ACEH - Miranda, Aja (Rabbani: Jurnal Pendidikan Agama Islam, 2022)
ABSTRACT School culture is a tangible form of the implementation of religious character in schools. It was to familiarize the religious character of the learner. school culture can manifest itself through islamic values, character, activity and religious symbols combined with other educational components.The study to discover: the form of school cultural programs, the administration of school cultures and the impact of school culture's success in building religious character. Research use a qualitative approach with the type of case study. Data collection with observation, interviews and documentation. Analysis used reduction, verification, presentation. Research: school culture program to building the religious character of participants that is: Reading Yasin's surah in the morning, pray dhuha and dzuhur, commemorating day of Islam, the performance talent, the performance of school culture to building religious character through Islamic values, Islamic activities and Islamic symbols and the success of the school's implementation of religious character.